Study of Treatment Process Improvement of Fecal Sludge in Surabaya City and Optimization for The Retribution Management - Farid Pratama Putra; Eddy Setiadi Soedjono; Ida Wahyuningsih (IPTEK Journal of Proceedings Series, 2020)
IPLT Keputih is one and only fecal sludge treatment plant in Surabaya City. As mentioned on Perda No 1 Tahun 2016 Kota Surabaya, fecal sludge is one of the public services with current retribution cost of Rp. 15.000/m3. However, the retribution cost does not cover all fecal sludge treatment cost, rather merely as indicator for public participation to treat their fecal sludge. Throughout 2014-2018, the number of treated fecal sludge in IPLT Keputih is 134.537,52 m3 while the fecal sludge potential is up to 2.756.146,5 m3. In order to increase public participation, it is necessary to review value and sytem of fecal sludge treatment and adjust it with local economic condition. In addition, to support the treatment potential, IPLT Keputih also needs some optimization in the retribution management. The method used in this study is started by collecting primary and secondary data about the treatment and retribution system. Laboratory test result will be the basic of process performance. After all data are complete, there will be some analysis based on the evaluation of process and operation, improvement process and operation recommendation based on process experiment, and retribution system optimization. To optimize the value of retribution and system, the optimal value of retribution and maximum service (treatment and desludging) is Rp. 12.000/month combined with PDAM retribution. This will in return increase public participation in fecal sludge treatment.